IMPROVING CONCEPTS UNDERSTANDING AFFECTED TEACHING MATERIALS USED IN CLASS VII COLLECTION MATERIALS - Dina Fiddiana (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
Mathematics is one of the very subjects that need to be studied, even mathematics is invited from elementary school to college level. In learning mathematics, we meet many students who have difficulty accepting the material being taught. Understanding mathematical concepts is very important for students, because mathematical concepts are interconnected with each other so they must be studied sequentially and continuously. One of the mathematics materials that students often have difficulty working on is set material. To overcome this, teachers must be able to innovate in providing teaching materials that are acceptable to students. With the existence of interesting teaching materials will make students more interested and able to understand the material .